2009
DOI: 10.1530/eje-09-0374
|View full text |Cite
|
Sign up to set email alerts
|

Association between hepatic steatosis and serum IGF1 and IGFBP-3 levels in a population-based sample

Abstract: Context: It is assumed that hepatic steatosis plays a role in the development and progression of the metabolic syndrome and its cardiovascular sequelae. Low serum IGF1 levels might mediate these associations. Objectives: The aims of this study were i) to investigate the associations of hepatic steatosis with serum IGF1 and IGF binding protein-3 (IGFBP-3) levels using ultrasound and serum alanine aminotransaminase (ALT) data to define hepatic steatosis, and ii) to analyze the specific role of alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 39 publications
(43 reference statements)
4
63
1
Order By: Relevance
“…Introduction of the parameter permitted us to additionally manifest the relatively more or less pronounced negative correlations of the parameter with several clinical data (age, grading, AFP concentration, staging). In our patients, we were not able to confirm the apparently evident coexistence of lowered S-IGF-1 and serum IGF-1/IGFBP-3 values and the highest IGFBP-3 levels with liver steatosis, reported earlier by other authors in their studies on isolated fatty degeneration of the liver (22) or non-alcoholic fatty liver disease and portal fibrosis (49). In the present study, quantitative evaluation of tissue IGFBP-3 expression in HCV-infected livers demonstrated a notably significant overexpression of the protein in CH-C patients as compared to the control and HCC patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Introduction of the parameter permitted us to additionally manifest the relatively more or less pronounced negative correlations of the parameter with several clinical data (age, grading, AFP concentration, staging). In our patients, we were not able to confirm the apparently evident coexistence of lowered S-IGF-1 and serum IGF-1/IGFBP-3 values and the highest IGFBP-3 levels with liver steatosis, reported earlier by other authors in their studies on isolated fatty degeneration of the liver (22) or non-alcoholic fatty liver disease and portal fibrosis (49). In the present study, quantitative evaluation of tissue IGFBP-3 expression in HCV-infected livers demonstrated a notably significant overexpression of the protein in CH-C patients as compared to the control and HCC patients.…”
Section: Discussioncontrasting
confidence: 99%
“…There are also data on elevated levels of S-IGF-1 and lowered levels of S-IGFBP-3 as compared to the control in chronic viral hepatitis (HCV or HBV) (30). Lower levels of S-IGFBP-3 were observed in liver steatosis (22), CH-C and liver cirrhosis (18,23,28,31). Serum levels of IGF-1 <30 ng/ml, IGF-2 <200 ng/ml and IGFBP-3 <6 ng/ml indicated a negative prognosis for patients with liver cirrhosis (28).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, acromegalic patients presenting with uncontrolled diabetes may have nonalcoholic fatty liver disease giving falsely low IGF-I levels. 1 The OGTT is the most specific dynamic test for establishing the diagnosis of acromegaly. It has been proposed that if both the GH value is less than 0.3 μg/L and the IGF-I is normal, then acromegaly may be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This would tend to support previous observations that MSG induces growth hormone perturbations in rodents (Hermanussen and Tresguerres 2003;RomanRamos et al 2011), accompanied by a reduction in serum IGF1 (Alponti et al 2011;Fernandez-Tresguerres 2005). IGF1 is derived mainly from the liver, and low serum IGF1 is associated with increased human hepatic steatosis (Völzke et al 2009). Diet A cat livers had increased expression of a number of genes related to hepatic steatosis, including DGAT1 (Millar et al 2006), perlipin (Fujii et al 2009), and fatty acid-binding protein 1.…”
Section: Discussionmentioning
confidence: 99%